Optimization and Dynamics of Distillation Column Using Aspen Plus®. (2016) - Taqvi, Syed A.; Tufa, Lemma Dendena; Muhadizir, Shuhaimi
Abstract: Ever increasing global energy demand necessitates the need to enhance energy generation and efficient utilization. As energy prices continue to rise, energy conservation is the prime concern for every industry. Distillation is probably the most studied unit operation in terms of optimization and control. Since distillation columns are major energy-intensive units in chemical plants and given the recent increase in fuel cost, the plant engineers are obliged to find better operating strategies and control systems. One of the significant sections that can be worked upon is finding the optimum feed tray locations of distillation columns. The energy consumptions during distillation can have a strong impact on overall profitability. Hence, the optimization of a column is aimed towards greater production and an increase in quality. Since a column is multivariable system, disturbance in any parameter can affect the overall performance as well as production loss. This paper shows how an acetone manufacturing process can be conveniently simulated first to get temperature, pressure and composition profile followed by application of optimization techniques to enhance performance. It was performed by the means of using a simulator Aspen Plus®. Rebolier heat duty (MW) and minimum reflux ratio were successfully optimized by manipulating feed stage location and number of stages respectively. It was observed that minimum reboiler duty is 40.8 MW when feed is at stage 10 resulting in 98% acetone as distillate.